2004
DOI: 10.1002/adsc.200404188
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Coupling of Triallyl(aryl)silanes with Aryl Bromides and Chlorides: An Alternative Convenient Biaryl Synthesis

Abstract: Cross-coupling of a diverse range of aryl bromides with triallyl(aryl)silanes is effective in the presence of PdCl 2 /PCy 3 and tetrabutylammonium fluoride (TBAF) in DMSO-H 2 O to give various biaryls in good yields. It is worthwhile to note that the all-carbon-substituted arylsilanes, stable towards moisture, acid, and base and easily accessible, serve as a highly practical alternative to their aryl(halo)silane counterparts. A catalyst system consisting of [(h 3 -C 3 H 5 )PdCl] 2 and 2-[2,4,6-(i-Pr) 3 C 6 H 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 70 publications
2
37
0
3
Order By: Relevance
“…[2] These phosphines have been used as ligands for gold, [3][4][5][6][7][8][9][10][11] silver, [12] rhodium, [13,14] ruthenium [15][16][17] and copper [18] where they have been shown to impart improvements in reactivity and catalyst stability. It is in reactions catalyzed by palladium, however, that they have had by far the greatest impact including the Sonogashira, [19] Negishi, [20] Hiyama, [21][22][23] Kumada [24] and Suzuki [25][26][27][28][29][30] cross-coupling reactions, Heck reaction, [31][32][33] enolate arylation [34][35][36][37] and allylation, [38] reductive cyclization [39] and etherification, [40][41][42][43] silylation, [44] borylation, [45][46][47] cyanation, [48,…”
Section: Introductionmentioning
confidence: 99%
“…[2] These phosphines have been used as ligands for gold, [3][4][5][6][7][8][9][10][11] silver, [12] rhodium, [13,14] ruthenium [15][16][17] and copper [18] where they have been shown to impart improvements in reactivity and catalyst stability. It is in reactions catalyzed by palladium, however, that they have had by far the greatest impact including the Sonogashira, [19] Negishi, [20] Hiyama, [21][22][23] Kumada [24] and Suzuki [25][26][27][28][29][30] cross-coupling reactions, Heck reaction, [31][32][33] enolate arylation [34][35][36][37] and allylation, [38] reductive cyclization [39] and etherification, [40][41][42][43] silylation, [44] borylation, [45][46][47] cyanation, [48,…”
Section: Introductionmentioning
confidence: 99%
“…17 Hiyama and co-workers utilized tri-, di-, and monoallyl(aryl)-silanes in Pd-coupling with aryl halides to access biaryls. 18 They suggested that allylsilanes spontaneously cleave upon treatment with TBAF and an appropriate amount of water to provide an active silicate species that promotes transmetalation. Although the chemistry of allylgermanes is well established, 19,20 the application of allyl organogermanes as substrates for the Pd-catalyzed crosscoupling with aryl halides has not been investigated.…”
mentioning
confidence: 99%
“…The amount of TBAF was found to be crucial However, attempts to induce multiple transfer of the phenyl group during fluoride-promoted couplings of (allyl) X Ph 4-X Si (x = 1 or 2) with aryl halides failed (23 and 24, Scheme 6, section 1.2.1.1). 105 It is viable that the germanium species with extra halogen ligands formed after each transmetallation cycle is rendered more reactive to efficiently transfer a second or third phenyl group from the Ge atom. Water might play multiple roles in enhancing the efficiency of the couplings as was found with organosilanes, including the formation of the reactive hydroxypalladium intermediates.…”
Section: Pd-catalyzed Cross-coupling Of Chlorophenylgermanesmentioning
confidence: 99%
“…The design of the germanes 125-127 was made based on the reported transfer of the phenyl/aryl group from the moderately reactive allyl(phenyl)silanes 23 105 and aryl(2-naphthylmethyl)germanes 28 106 (see section 1.2.1.1).…”
Section: Allyl(phenyl)germanes As Substrates For the Pd-catalyzed Cromentioning
confidence: 99%
See 1 more Smart Citation